The Thomas Chandler Haliburton Symposium. - Tierney, Frank (University of Ottawa Press, 1985)
Thomas Chandler Haliburton was perhaps the only Canadian writer whose name was a household word in nineteenth-century Canada. The ten papers in this volume reappraise the historical, geographical, political and literary contexts within which Haliburton lived and worked. His letters, his historical books, the Club papers and Sam Slick sketches are all included in these valuable and lively criticisms.